Histone Ubiquitination: An Integrative Signaling Platform in Genome Stability - Mattiroli, Francesca; Penengo, Lorenza (Trends in genetics, 2021)
Complex mechanisms are in place to maintain genome stability. Ubiquitination of chromatin plays a central role in these mechanisms. The ever-growing complexity of the ubiquitin (Ub) code and of chromatin modifications and dynamics challenges our ability to fully understand how histone ubiquitination regulates genome stability. Here we review the current knowledge on specific, low-abundant histone ubiquitination events that are highly regulated within the cellular DNA damage response (DDR), with particular emphasis on the latest discovery of Ub phosphorylation as a novel regulator of the DDR signaling pathway. We discuss players involved and potential implications of histone (phospho)ubiquitination on chromatin structure, and we highlight exciting open questions for future research. Histones are heavily post-translationally modified by ubiquitin. Lately, many more ubiquitin-based modifications have been mapped on histones, which are far less abundant than the canonical ones but essential to safeguard genome stability.Histones at damaged DNA can be modified by phospho-ubiquitin (i.e., pUb at Thr12), resulting in chromatin regions with new properties that impact DNA repair pathways.The discovery of new ubiquitination sites on histones and new ubiquitin modifications expands dramatically the landscape of chromatin-based signaling and crosstalk, paving the way for future studies on novel mechanisms in genome stability programs (i.e., new writers, readers, and erasers).